Law of bias and mala fides( Judicial and administrative) - Misra, A.S. (Lucknow, 2007)
This book explain the law of suspension is well settled and the present work lucidly explains the law on the subject in the light of decided cases. This book explain the principles relating to scope of suspension, consequences of suspension, automatic or deemed suspension, authority competent to suspend, justification of order, period of suspension, subsistence allowance, reinstatement, and other allied aspects relating to suspension.
Keywords: Bias